1968
DOI: 10.1901/jaba.1968.1-139
|View full text |Cite
|
Sign up to set email alerts
|

RULES, PRAISE, AND IGNORING: ELEMENTS OF ELEMENTARY CLASSROOM CONTROL1

Abstract: An attempt was made to vary systematically the behavior of two elementary school teachers to determine the effects on classroom behavior of Rules, Ignoring Inappropriate Behaviors, and showing Approval for Appropriate Behavior. Behaviors of two children in one class and one child in the other class were recorded by observers, as were samples of the teachers' behavior. Following baseline recordings, Rules, Ignoring, and Approval conditions were introduced one at a time. In one class a reversal of conditions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
187
1
3

Year Published

1971
1971
1973
1973

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(198 citation statements)
references
References 3 publications
7
187
1
3
Order By: Relevance
“…For example, Surrat, et al, (1969) suggested a relationship between attending behavior and academic achievement: "The 'working' behaviors modified in the present experiments are assumed to be correlated with the actual accomplishment of assigned work and ultimately with academic achievement (page 91)." Other relationships, such as between attending behavior and affective or even self-improving behavior are also posited, Madsen, et al, (1968) This study, however, suggests that contingencies that increase attending behavior and reduce disruptions do not necessarily increase student performance, at least in arithmetic drill exercises. Contingencies on attending alone increased attending behavior and decreased disruptive behavior, but had little effect on the measures for correct work accomplished.…”
Section: Social Behaviormentioning
confidence: 66%
“…For example, Surrat, et al, (1969) suggested a relationship between attending behavior and academic achievement: "The 'working' behaviors modified in the present experiments are assumed to be correlated with the actual accomplishment of assigned work and ultimately with academic achievement (page 91)." Other relationships, such as between attending behavior and affective or even self-improving behavior are also posited, Madsen, et al, (1968) This study, however, suggests that contingencies that increase attending behavior and reduce disruptions do not necessarily increase student performance, at least in arithmetic drill exercises. Contingencies on attending alone increased attending behavior and decreased disruptive behavior, but had little effect on the measures for correct work accomplished.…”
Section: Social Behaviormentioning
confidence: 66%
“…Thus, the majority of investigators have examined interactions between parents and their children (e.g., Patterson, Cobb, and Ray, in press) or between teachers and their pupils (e.g., Madsen, Becker, and Thomas, 1968). Based partly on information derived from these assessments, training programs have been devised to shift adult social attention from the children's problem behavior to their more desirable actions.…”
mentioning
confidence: 99%
“…Even when observational codes include nonverbal teacher behaviors such as facial expressions and physical contact (Becker et al, 1967) or proximity of the teacher to the pupil , it remains unclear whether these behaviors contribute to behavior change in the students independently of verbal approval alone. One reason that nonverbal attending behavior usually is not evaluated is that verbal approval, as opposed to facial expressions and physical contact, constitutes most (about 85 %) of teacher attending behavior (Madsen, Becker, and Thomas, 1968). Moreover, teacher training is more likely to emphasize and alter verbal behavior as opposed to nonverbal behaviors (facial expressions and physical contact) (Kazdin, in press).…”
mentioning
confidence: 99%